Organizational Profitability of Manufacturing Companies listed on the Ghana Stock Exchange - Kumi, John Adu; Martin Amaniampong; Mary Adu Kumi (IJRDO - Journal of Business Management, 2019)
Profitability is one of the most important objectives of financial management because one goal of financial management is to maximize the owner’s wealth. Hence profitability becomes very important determinant of company performance. The purpose of this study is to investigate the effect of corporate income tax and liquidity on profitability of manufacturing companies listed at the Ghana Stock Exchange. Profitability is the dependent variable while corporate income tax and liquidity are the independent variables. The sample in this study includes four listed manufacturing companies on the Ghana Stock Exchange for over five years. Correlations of variables and regression analysis revealeda negative relationship between profitability of manufacturing companies and corporate income tax to show that corporate income tax has negative effect on company profitability. However, a positive and significant correlation was established between liquidity and profitability on manufacturing companies. Liquidity is positive and significant in predicting the profitability of manufacturing companies with p-value = 0.006. This implies that a unit increase in the company liquidity will lead to 0.006 increase in company profitability.